2014
DOI: 10.1242/dev.111906
|View full text |Cite
|
Sign up to set email alerts
|

BMP-mediated induction of GATA4/5/6 blocks somitic responsiveness to SHH

Abstract: The relative timing of SHH and BMP signals controls whether presomitic mesoderm (PSM) cells will adopt either a chondrogenic or lateral plate mesoderm fate. Here we document that SHH-mediated induction of Nkx3.2 maintains the competence of somitic cells to initiate chondrogenesis in response to subsequent BMP signals by repressing BMP-dependent induction of GATA genes. Conversely, administration of BMP signals to PSM or forced expression of GATA family members in chick PSM explants blocks induction of hedgehog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…In addition, there was a notable upregulation of many components of the hedgehog pathway, suggesting that the major mechanism of GATA4/6-regulated pancreas development is through suppression of the hedgehog pathway. Previous studies have demonstrated that GATA factors can negatively regulate Shh expression in the stomach, limb bud, and somites (Daoud et al, 2014;Jacobsen et al, 2005;Kozhemyakina et al, 2014). Our studies suggest that GATA4 and GATA6 pattern the foregut endoderm through the repression of hedgehog signaling.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…In addition, there was a notable upregulation of many components of the hedgehog pathway, suggesting that the major mechanism of GATA4/6-regulated pancreas development is through suppression of the hedgehog pathway. Previous studies have demonstrated that GATA factors can negatively regulate Shh expression in the stomach, limb bud, and somites (Daoud et al, 2014;Jacobsen et al, 2005;Kozhemyakina et al, 2014). Our studies suggest that GATA4 and GATA6 pattern the foregut endoderm through the repression of hedgehog signaling.…”
Section: Introductionsupporting
confidence: 61%
“…During gastric development, Gata4 and Shh expression is mutually exclusive, suggesting that GATA4 might inhibit the expression of Shh (Jacobsen et al, 2005). In the limb bud, GATA6 was shown to inhibit Shh gene expression through a limb bud-specific enhancer of the Shh gene , and in the somitic system, GATA4/5/6 were found to inhibit Shh signaling by inhibiting Gli1 expression, although direct inhibition of Shh was not required (Daoud et al, 2014). The upregulation of hedgehog pathway expression in the pDKO mice suggested that Shh might be repressed by GATA4 and/or GATA6.…”
Section: Cell Fate Switching Occurs In the Pdko Pancreatic Endodermmentioning
confidence: 99%
“…GATA1/2 transcription factors have known binding sites in the GLI1 and SHH promoters, 42 and GATA6 is known to suppress the SHH gene in limb development. 43,44 Using chromatin immunoprecipitation, we confirmed binding of GATA1 to 2 predicted regions of the GLI1 promoter in HSB2, a T-ALL cell line that expresses GATA1 (supplemental Figure 4). In addition, NF-kB2 was found to be positively correlated with SHH, IHH, and GLI1 expression (supplemental Figure 3).…”
Section: Resultsmentioning
confidence: 69%
“…Nkx3-2 is a BMP-dependent transcriptional repressor (Kim and Lassar, 2003) that blocks the expression of inhibitor(s) of Sox9 transcription (Zeng et al, 2002). It was recently found that Nkx3-2 blocks BMPdependent expression of several GATA transcription factors (Gata4, Gata5 and Gata6) in explants of paraxial mesoderm, and that these GATA factors can in turn block Shh-dependent induction of Sox9 gene expression (Daoud et al, 2014) (Fig. 3).…”
Section: Shh Induces Chondrogenic Competence In Sclerotomal Cells By mentioning
confidence: 94%